The Impact of Online Customer Reviews and Online Customer Ratings on Consumer Trust in Roughneck 1991 Products - Ibrahim, Feri; Isyanto, Puji; Sumarni, Neni (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this research is to determine whether positive or negative online reviews impact consumer trust in a business. The investigation methodology is quantitative. Active management students from the class of 2019 who have purchased Roughneck 1991 products on the Shopee Marketplace constitute the population for this analysis. A total of 94 participants were surveyed for this analysis. Primary data collection was conducted by sending out questionnaires, thus this research relies entirely on this method. Multiple regression analysis in SPSS 25 was used to analyze the data in this study. The t-test findings of this study indicate that positive online customer reviews significantly increase consumer trust, whereas online customer ratings do not. Consumer trust in Roughneck 1991 products on the Shopee Marketplace has increased as a result of statistically significant positive feedback they receive from other customers' evaluations and ratings posted online. It is expected that in the future, academics will include more characteristics that theoretically also impact customer trust. Researchers can provide marketing advice to Roughneck 1991 to improve the quality and quantity of their merchandise. Roughneck has tremendous potential to expand its market share thanks to the positive feedback they will receive from satisfied customers if they continue to improve the quality of their products.